Bioremediation of an Iron-Rich mine effluent by Lemna minor - Teixeira, S.
Contamination of water resources by mine effluents is a serious environmental problem. In a old coal mine, in the north of Portugal (São Pedro da Cova, Gondoma),forty years after the activity has ended, a neutral mine drainage, rich in iron (FE) it stills being produced and it is continuously released in local streams (Ribeiro de Murta e Rio Ferreira) and in surrounding lands. The species Lemna minor has been shown to be a good model for ecotoxicological studies and it also has the capacity to bioaccumulate metals. The work aimed test the potential of the species L. minor to remediate this mine effluent, through the bioaccumulation of Fe, under greenhouse experiments and, at the same time, evaluate the time required to the maximum removal of Fe. The results have shown that L. minor was able to grow and develop in the Fe-rich effluent and bioaccumulating this element. Throughout the 21 days of testing it was found that there was a meaningful increase in the biomass of L. minor both in the contaminated and in the non-contaminated waters. It was also found that bioaccumulation of Fe (iron) occurred mainly during the first 7 days of testing. It was found that L. minor has potential for the bioremediation of effluents rich in iron.